Kantor Sewa Di Pekanbaru Dengan Pendekatan Pencahayaan Alami - Nasution, Fajar Rizki; Aldy, Pedia; Novan, Andre (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Office is one of fundamental basic when starting a company. But, due to its high cost of building a new office, many consider to rent, wether its a small space, or even a whole building. In adeveloping city like Pekanbaru, to build a new building must follow the aspect of sustainable design, such as to consider building a high-rise instead of a multi-storey building. Talk about ahigh-rise building, expecially one designed for office, the use of electricity is inevitably high. For example, the use for lighting, cooling system, and the use of all other office equipment (computer, fotocopy machine, etc) which is very active during the worktime. But, there’s actually a solution to this, as office mostly active during the day. And that is the very reason to consider the use of infinite source of energy during the day, the daylight itself. The designing of natural lighting strategy basedon the elements of : building orientation, toplighting, sidelighting, and shading system. The application of natural lighting concept on this building will reduce the cost of electricity andbecome an eco-friendly building.Keywords : Office, Rental Office, Natural Lighting